Model Rapid Application Development (RAD) Untuk Perancangan Sistem Informasi Pengelolaan Surat (SIPERA) Pada Kelurahan - Dalis, Sopiyan; Agustiani, Sarifah; Bahri, Syamsul; Wahyudin, Wahyudin; Prawikas, Amanda (LPPM Universitas Bina Sarana Informatika, 2024)
Every government institution must have its own method of managing correspondence, either through a computerized system or still using a manual approach. In the context of managing incoming mail and outgoing mail in some institutions, there is the use of a manual approach that sometimes creates obstacles and constraints. One of the problems that often arises is the difficulty in finding data due to the excessive accumulation of letter archives. A similar situation is also encountered at the Muarasari Village Office, South Bogor Subdistrict, Bogor City, where the manual method used makes the process of searching for letters complicated and time-consuming. In order to overcome these problems, this research aims to design a computer-based incoming and outgoing mail management system to improve efficiency and effectiveness in managing these letters. In an effort to design a mail management system, the research approach involved interviews, observations, and using the Rapid Application Development (RAD) methodology, which emphasizes software development with relatively short time and the ability to adapt to changes. Through the implementation of this computerized mail management system, it is expected that the challenges in managing incoming and outgoing mail at the Muarasari Village Office can be overcome. Thus, this system is expected to increase efficiency and effectiveness in the management of letters, help improve the search process, and support overall improvement in the management of incoming and outgoing letters.